INTRANSITIVE PHRASAL VERBS WITH PARTICLE 'THROUGH' IN BRITISH NATIONAL CORPUS - Diana Anggraeni (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2019)
The aim of this study is to describe the intransitive phrasal verbs with particlethrough used in the British National Corpus. The method used in this research is descriptive qualitative method. Linguistic data sources were taken from the British National Corpus. The data containing the phrasal verbs with particle through, collected and then classified into several categories. The categories that are suitable for the purpose of the research are separated and labeled and then explained in a narrative according to the theory and research objectives. The results showed that the intransitive phrasal verbs with particle through in the British National Corpus consisted of two types, namely dynamic and stative intransitive phrasal verbs. Dynamic intransitive is a phrasal verbs with a particle through which indicates the existence of an activity or event carried out by the subject of the sentence. Dynamic intransitive phrasal verbs consist of phrasal verbs belonging to event verbs and activity verbs. Stative intransitive phrasal verbs are classified as existence verbs.